2017
DOI: 10.1007/s40069-017-0196-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Proportion of Masonry Chip Aggregate for Internally Cured Concrete

Abstract: Proper curing of concrete is essential for achieving desirable mechanical properties. However, in a developing country like Bangladesh, curing is often neglected due to lack of proper knowledge and skill of local contractors. Consequently, general concreting work of the country has been found to have both strength and durability issues. Under such scenario, internal curing could be adopted using masonry chip aggregate (MCA) which is quite common in this region. It is observed that saturated MCA desorbs water u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 13 publications
1
0
0
Order By: Relevance
“…It is well known that the mechanical properties of concrete are highly influenced by its density. A denser concrete generally provides higher strength [13]. Previous research by Aoki [14] indicated the same trend as the current study.…”
Section: Density and Compressive Strengthsupporting
confidence: 88%
“…It is well known that the mechanical properties of concrete are highly influenced by its density. A denser concrete generally provides higher strength [13]. Previous research by Aoki [14] indicated the same trend as the current study.…”
Section: Density and Compressive Strengthsupporting
confidence: 88%